Динамическая неустойчивость обтекателей ракет-носителей в полете - Чернобрывко, М.В.; Аврамов, К.В.; Романенко, В.Н.; Батутина, Т.Я.; Пирог, В.А. (Проблемы машиностроения, 2014)
Исследуется динамическая неустойчивость обтекателей ракет-носителей в полете. Так как большую часть полета ракета движется со сверхзвуковой скоростью, то для описания давления газа, действующего на обтекатель, применяется поршневая теория. Обтекатель ракеты-носителя описывается параболической оболочкой. Для вывода уравнений колебаний применяется метод заданных форм. Исследуются свойства колебаний обтекателя. Досліджується динамічна нестійкість обтічників ракетносіїв у польоті. Оскільки більшу частину польоту ракета рухається з надзвуковою швидкістю, то для опису тиску газу, що діє на обтічник, застосовується поршнева теорія. Обтічник ракети-носія описується параболічною оболонкою. Для отримання рівнянь коливань застосовується метод заданих форм. Досліджуються властивості коливань обтічника. The equations of the parabolic shell motions are obtained using the assumed- modes method. It is obtained the system of the ordinary differential equations described the parabolic shell vibrations in a supersonic flow. The approach for calculation of the shape of the shell self- sustained vibrations origin is suggested. The dynamic instability of the parabolic shells is analyzed numerically. The properties of the shell vibrations are investigated. The unstable equilibrium of the paraboloic shell in the supersonic gas stream is observed in the following range of the Mach number: 1< М ≤ 1.4142. The critical Mach number is not changed, if the height of the shell is increased from 2m to 4 m. This is explained by violent vibrations, which are observed in the shell bottom. The frequencies of the self- sustained vibrations are significantly larger, then the lower eigenfrequencies of the shell. If the height of the shell is increased, the frequency of the self- sustained vibrations is increased too. Note, that the shell eigenfrequencies are decreased, if the shell height is increased.